STRATEGY INSTALLATION OF RELIGIOUS VALUES IN PUTIH VILLAGE CHILDREN THROUGH HABITATION METHOD - Ana Lailatul Mafazah (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2022)
Religious cultivation in children is essential in today's era. Especially during this free association. The lack of education that children receive also causes a crisis of morality in children. Writing this article aims to instil religious values ​​to create akhlaq karimah in children through Habituation. The approach method is the Asset Based Community Development (ABCD) method which focuses on asset development. From the results, it has been concluded that: 1. Habituation in morals includes Habituation in morals including, S3 (Smile, Salim, Greetings) to others or older. 2. Habituation in worship includes starting activities by reading